PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PEMOHON SERTIFIKAT TANAH - Tri Wera Agrita; Titis Wulandari (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
The essence of the public service vision is the realization of excellent public services, which means being able to realize community satisfaction in an effort to get services from government agencies. This study aims to determine the effect of service quality on community satisfaction of applicants for land certificates in Bungo Regency. This research is descriptive by using survey data collection techniques which aim to determine the effect of two or more variables at the District National Land Agency Office. This study uses quantitative methods (statistical calculations) with simple linear regression using statistical analysis of Product Correlation Coefficients. A total of 100 samples came from applicants for land certificates using accidental sampling technique and distributing questionnaires filled out by respondents. The results of the analysis of hypothesis testing found that there was a positive and significant effect of the service of officers on community satisfaction in managing land certificates. The statement of the hypothesis that there is a positive and significant effect of officer services on community satisfaction in managing land certificates is proven, which means that the stronger the service of officers, the stronger the community's satisfaction in managing land certificates. This is indicated by the value of t table which is smaller than t count (1.661) < t arithmetic (6.666), and a significance value (0.000) which is smaller than 0.05 and a regression coefficient of 0.559.